Why do adults go to adult secondary school? - Donvito, Angel Eduardo (2019)
This paper analyzes the motivation of adult students to attend Adult Secondary Education (ASE) in Argentina. The investigation consisted of an exploration stage using the Focus Groups technique (FG) in which 29 ASE students participated, then a stage of analysis and construction of a survey based on the results of the FG, and finally, a stage of implementation and analysis of the survey, which was administered to 820 adult students nationwide. The results show that students' motivation is related to three aspects: improving job position, improving self-esteem and preparing to study a career. Furthermore, these aspects are not isolated, but are significantly associated with each other. Considering the students' motivation to attend the ASE both in the curricular conformation and at classrooms, could be a way to improve not only the teaching but also the quality of life of adults.